EXPLORING THE CORRELATION BETWEEN CORPORATE SOCIAL RESPONSIBILITY INDICATORS AND CORPORATE REPUTATION : CASE STUDY OF LEGO GROUP 2012–2023 - Mohamed BOULESNAM; Abdelghani KAHELA; Ouissam HOCINI (Modern Management Review)
This study examines the correlation between Corporate Social Responsibility (CSR) indicators and LEGO Group’s corporate reputation from 2012 to 2023. Using quantitative analysis, the research investigates the relationship between key CSR metrics, such as environmental, employee, and customer-focused initiatives, and their impact on LEGO’s reputation ranking as measured by the RepTrak platform. The findings reveal a strong positive correlation between waste management efforts, particularly waste to landfill, and corporate reputation, while water consumption and injury rates show strong negative and positive correlations, respectively. Other indicators, including carbon emissions, community engagement, and employee satisfaction, show weaker correlations. The study underscores the importance of environmental management and workplace safety in enhancing corporate reputation while highlighting areas where CSR practices contribute less significantly to reputation. These insights contribute to understanding how CSR practices shape public perception and business success over time.